Palembang City In Time: A History of Social And Cultural Change - Azizah, Faras Puji; Sudarman, Sudarman; hakim, Lukmanul; Syabilah, Nur ‘Afifah; Fariza, Nur Anis (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article discusses the history of Palembang, which can provide many exciting things to learn more about this city, such as its history, culture, and even culinary aspects. This article aims to find out the origin and background of the formation of Palembang's colonial cities and towns, as well as to find out the state of society during the colonial period and also to find out the symbolic post-colonial Palembang city. This research uses the historical method through four stages: Heuristics, Source Criticism, Interpretation, and Historiography. The result of this research is that there has been a change in the order of Palembang city from river to land carried out by the colonial government. The community activity here is trade; the economy of the Palembang people is very successful, where the price of rubber, coffee, and sap is expensive, so the Palembang people are nicknamed the Golden Rain. After Indonesia's independence, a symbolic building of Palembang was built, the Ampera Bridge.